The medial femoral condyle free osteocutaneous flap for osteomyelitis in pilon fractures. Issue 2 (February 2015) - Caterson, Edward J.; Singh, Mansher; Turko, Arthur; Weaver, Michael J.; Talbot, Simon
Abstract Background High energy tibial plafond (pilon) fractures are known to have a high rate of complication, particularly wound dehiscence and infection. Wound infection, requiring debridement of both soft tissue and bone can be especially challenging to reconstruct due to the combination of high load-bearing requirements within a thin soft tissue envelope. Method We present a case of a pilon fracture with a post-operative complication of wound dehiscence and infection necessitating bone debridement, ultimately resulting in chronic osteomyelitis. We used a medial femoral osteocutaneous free flap to provide vascularised structure to the defect. Included is a comprehensive literature review for the use of the MFC osteocutaneous free flaps in lower extremities. Results This flap provided restoration of the medial column of the ankle. The use of vascularised bone resulted in rapid post-operative bony union. The vascularised bone flap was press fit into the defect ruling out the potential for further hardware related infections. We report follow up of over one year. Conclusion The MFC free osteocutaneous flap is a good option for small bone and soft tissue defects of lower extremities, especially in setting of chronic osteomyelitis. It can be custom fabricated and either fixated or press fit into a chronic pilon fracture cavity to obliterate dead space with vascularised bone. Level of evidence Level IV, retrospective case study.